Antagonistic postsynaptic and presynaptic actions of cyclohexanol on neuromuscular synaptic transmission and function. (26th November 2021) - Dissanayake, Kosala N.; Margetiny, Filip; Whitmore, Charlotte L.; Chou, Robert C.‐C.; Roesl, Cornelia; Patel, Vishwendra; McArdle, Joseph J.; Webster, Richard; Beeson, David; Tattersall, John E.H.; Wyllie, David J. A.; Eddleston, Michael; et al.
Abstract : Abstract: Intentional ingestion of agricultural organophosphorus insecticides is a significant public health issue in rural Asia, causing thousands of deaths annually. Some survivors develop a severe, acute or delayed myasthenic syndrome. In animal models, similar myasthenia has been associated with increasing plasma concentration of one insecticide solvent metabolite, cyclohexanol. We investigated possible mechanisms using voltage and current recordings from mouse neuromuscular junctions (NMJs) and transfected human cell lines. Cyclohexanol (10–25 mM) reduced endplate potential (EPP) amplitudes by 10–40% and enhanced depression during repetitive (2–20 Hz) stimulation by up to 60%. EPP decay was prolonged more than twofold. Miniature EPPs were attenuated by more than 50%. Cyclohexanol inhibited whole‐cell currents recorded from CN21 cells expressing human postjunctional acetylcholine receptors (hnAChR) with an IC50 of 3.74 mM. Cyclohexanol (10–20 mM) also caused prolonged episodes of reduced‐current, multi‐channel bursting in outside‐out patch recordings from hnAChRs expressed in transfected HEK293T cells, reducing charge transfer by more than 50%. Molecular modelling indicated cyclohexanol binding (−6 kcal/mol) to a previously identified alcohol binding site on nicotinic AChR α‐subunits. Cyclohexanol also increased quantal content of evoked transmitter release by ∼50%. In perineurial recordings, cyclohexanol selectively inhibited presynaptic K + currents. Modelling indicated cyclohexanol binding (−3.8 kcal/mol) to voltage‐sensitive K + channels at the same site as tetraethylammonium (TEA). TEA (10 mM) blocked K + channels more effectively than cyclohexanol but EPPs were more prolonged in 20 mM cyclohexanol. The results explain the pattern of neuromuscular dysfunction following ingestion of organophosphorus insecticides containing cyclohexanol precursors and suggest that cyclohexanol may facilitate investigation of mechanisms regulating synaptic strength at NMJs. Key points: Intentional ingestion of agricultural organophosphorus insecticides is a significant public health issue in rural Asia, causing thousands of deaths annually. Survivors may develop a severe myasthenic syndrome or paralysis, associated with increased plasma levels of cyclohexanol, an insecticide solvent metabolite. Analysis of synaptic transmission at neuromuscular junctions in isolated mouse skeletal muscle, using isometric tension recording and microelectrode recording of endplate voltages and currents, showed that cyclohexanol reduced postsynaptic sensitivity to acetylcholine neurotransmitter (reduced quantal size) while simultaneously enhancing evoked transmitter release (increased quantal content). Patch recording from transfected cell lines, together with molecular modelling, indicated that cyclohexanol causes selective, allosteric antagonism of postsynaptic nicotinic acetylcholine receptors and block of presynaptic K + ‐channel function. The data provide insight into the cellular and molecular mechanisms of neuromuscular weakness following intentional ingestion of agricultural organophosphorus insecticides. Our findings also extend understanding of the effects of alcohols on synaptic transmission and homeostatic synaptic function. Abstract : Abstract figure legend Cyclohexanol, the principal metabolite of a common agricultural insecticide solvent, cyclohexanone, acts both presynaptically and postsynaptically to impair neuromuscular transmission. (1) Cyclohexanol binds to sites in the pore of voltage‐sensitive K + channels that also bind the K + channel blocker tetraethylammonium (TEA), with the effect of reducing presynaptic motor nerve terminal K + currents and increasing quantal content of evoked transmitter release. (2) Simultaneously, cyclohexanol binds allosterically to an alcohol binding site on postsynaptic nicotinic acetylcholine receptors, altering ligand‐gating characteristics and reducing charge transfer. The combined, overall effects of (1) and (2) result in reduced amplitude, prolonged depolarization and enhanced synaptic depression of endplate potentials (EPPs), weakening tetanic tension responses and causing fade in twitch responses to low frequency nerve stimulation. These effects mimic myasthenia or paralysis that occur in self‐harming individuals who have swallowed significant quantities of organophosphorus insecticide, a significant public health issue in rural Asia. The present findings therefore provide an explanation for these clinical signs and indicate potential utility of cyclohexanol in further study of mechanisms of neuromuscular synaptic homeostasis.